Describe the Night - Joseph, Rajiv (Oberon Modern Plays, 2017)
In 1920, the Russian writer Isaac Babel wanders the countryside with the Red Cavalry. In 1990, a mysterious KGB agent spies on a woman in Dresden and falls in love. In 2010, an aircraft carrying most of the Polish government crashes in the Russian city of Smolensk. Set in Russia over the course of Ninety years, this thrilling and epic new play by Rajiv Joseph traces the stories of seven men and women connected by history, myth and conspiracy theories.